PENERAPAN METODE PEMBELAJARAN PQ4R UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XI SMA MUHAMMADIYAH 1 METRO - Triani Ratnawuri; Ahkaf Fikri; Siti Suprihatin (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The development of science and technology is growing rapidly. This requires the existence of quality human beings so as to be able to create new innovations and be able to face competition. Education is a pursuit of school for children and adolescents who are handed over to them to have perfect skills and full awareness of their social relationships and tasks. The 2013 curriculum goal is to prepare Indonesian people to have the ability to live as the individu and citizens who are faithful, productive, creative, innovative, and affective and able to contribute to the life of society, nation, state and world civilization. The problem formulation of this class action research is how is the effect of the application of PQ4R learning methods to improve learning outcomes of economic subjects at XI grade students of Senior High School Muhammadiyah 1 Metro